Prevalence And Associated Risk Factors Of Eimeria In Sheep Of Punjab, Pakistan - M.N. Khan; T. Rehman; Z Iqbal; M.S Sajid; M Ahmad; M Riaz (Zenodo, 2011)
A cross-sectional study was carried out to determine the prevalence, species characterization and associated risk factors with Eimeria (E.) in sheep of district Toba Tek Singh from April, 2009 to March, 2010. Of the total 486 faecal samples examined for Eimeria, 209 (43%) were found infected with five species of Eimeria. Amongst the identified species of Eimeria, E. ovinoidalis was the commonest one (48.32%), followed in order by E. ahsata, E. intricata, E. parva and E. faurei with prevalence of 45.45, 28.71, 24.40 and 19.14 percent respectively. Peak prevalence was observed in August. Wet season (rainy and post-rainy) was found to be favourable for Eimeria infection. Lambs had significantly higher prevalence (P < 0.05) of Eimeria than adults. Similarly higher prevalence of Eimeria was observed in female as compared to male. Among management and husbandry practices; watering system, housing system, floor type and herd size strongly influenced the prevalence of Eimeria. Coccidiosis was more prevalent in closed housing system, non-cemented floor type, pond watered animals and larger herds (P < 0.05) as compared to open housing system, partially cemented floor type, tap watered animals and smaller herds respectively. Feeding system, breed and body condition of animals were not found as risk factors (P>0.05) influencing prevalence of Eimeria. : {"references": ["Abebe, R., Wossene, A., Kumsa, B., 2008. Epidemiology of Eimeria\nInfections in Calves in Addis Ababa and Debre Zeit Dairy Farms,\nEthiopia. Int. J. Appl. Res. Vet. Med. 6, 24-30.", "Agyei, A.D., M. Odonkor and A. Osei-Somuah, 2004. Concurrence of\nEimeria and helminth parasitic infections in West African Dwarf kids in\nGhana. Small Ruminant Research, 51: 29-35", "Alzieu, J.P., C. Mage, L. Maes and C. de M\u2566\u00e5uelenaere, 1999. Economic\nbenefits of prophylaxis with diclazuril against subclinical coccidiosis in\nlambs reared indoors. Vet. Rec. 144; 442-444.", "Bauer, C., 1989. Infektionen mit Nematodirus battus (CROFTON und\nTHOMAS, 1951) und Weide-Eimeriose bei Schafl\u251c\u00f1mmern in\nDeutschland (Fallbericht). Dtsch. Tier\u251c\u00f1rztl. Wochenschr. 96, 382-384.", "Berriatua, E., Green, L.E., Morgan, K.L., 1994. A descriptive\nepidemiological study of coccidiosis in early lambing housed flocks.\nVet. Parasitol. 54, 337-351.", "Biu, A.A., A. Maimunatu, A.F. Salamatu and E.T. Agbadu, 2009. A\nfaecal survey of gastrointestinal parasites of ruminants on the University\nof Maiduguri Research Farm. International Journal of Biomedical and\nHealth Sciences, 5: 175-179.", "Chandrawathani P., R. Nurulaini, M. Adnan, B. Premalaatha, S.1.\nKhadijah, O. Jamnah, C.M. Zaini, S.K. Khor and Z. Zawida, 2009. A\nsurvey of parasitic infection on small ruminant farms in Kinta and Hilir\nPerak districts, Perak, Malaysia. Tropical Biomedicine, 26: 11-15", "Gauly, M., J. Reeg, C. Bauer and G. Erhardt, 2004. Influence of\nproduction systems in lambs on the Eimeria oocyst output and weight\ngain. Small Ruminant Research, 55: 159-167", "Iqbal, Z., Sajid, M.S., Jabbar, A., Rao Z.A., Khan, M.N. (Eds.), 2006.\nTechniques in Parasitology. Higher Education Commission, Islamabad-\nPakistan. pp, 52-54.\n[10] Kanyari, P.W.N., 1990. Prevalence of coccidian oocysts in sheep and\ngoat faecal samples. A preliminary report based on laboratory records.\nBull. Anim. Hlth. Prod. Afri. 38, 473-474.\n[11] Kaya, G., 2004. Prevalence of Eimeria Species in Lambs in Antakya\nProvince. Turkish Journal of Veterinary and Animal Science, 28: 687-\n692\n[12] Kusiluka, L.J.M., Kambaragea, D.M., Harrisonb, L.J.S., Dabornb C.J.,\nMatthewman, R.W., 1998. Prevalence and seasonal patterns of coccidial\ninfections in goats in two ecoclimatic areas in Morogoro, Tanzania.\nSmall Rumin. Res. 30, 85-91.\n[13] Levine, N.D. (Ed.), 1961. Protozoan Parasites of Domestic Animals and\nMan. Burgess Publishing Company, Minneapolis, pp, 189.\n[14] MAFF, 1986. Manual of Veterinary Parasitological Laboratory\nTechniques. ADAS, HMSO, UK.\n[15] McKellar, A.Q., 2008. Gastrointestinal Parasites of Ruminants. In:\nKahn, C.M., Line, S., Aiello, S.E. (Eds.), The Merck Veterinary Manual.\nWhitehouse Station, NJ, USA.\n[16] Pout, D.D., 1973. Coccidiosis of lambs. I. Observations on the naturally\nacquired infection. Br. Vet. J. 129, 555-567.\n[17] Radostits, O.M., Blood, D.C., Gay, C.C. (Eds.), 2009. Veterinary\nMedicine. A Textbook of the Diseases of Cattle, Sheep, Pigs, Goats, and\nHorses. Philadelphia, PA: Bailliere Tindall, London. pp, 1181- 1199.\n[18] Rommel, M., 2000. Parasitosen der Wiederk\u251c\u00f1uer (Rind, Schaf, Ziege)\n[Parasites of ruminants (Cattle, Sheep, Goats)]. In: Rommel M, Eckert J,\nKutzer E, K\u00f6rting W & Schnieder T (eds.) Veterin\u251c\u00f1rmedizinische\nParasitologie. Parey Buchverlag, Berlin, pp. 121-191 (In German).\n[19] Ruiz, A., J. F. Gonza'lez, E. Rodr\u2500\u2592'guez, S. Mart\u2500\u2592'n, Y. I. Herna'ndez, R.\nAlmeida and J. M. Molina, 2006. Influence of climatic and management\nfactors on Eimeria infections in goats from semi-arid zones. The Journal\nof Veterinary Medical Science., 53: 399-402\n[20] SAS, 1998. SAS/STAT User Guides version 6.12. SAS Inst. Inc., Cary,\nNC.\n[21] Sisodia, SL., K.M.L. Pathak, M. Kapoor and P.P.S. Chauhan, 1997.\nPrevalence and seasonal variation in Eimeria infection in sheep in\nwestern Rajasthan. Journal of Veterinary Parasitology, 11: 95-98.\n[22] Skirnisson, K., 2007. Eimeria spp. (Coccidia, Protozoa) infections in a\nflock of sheep in Iceland: Species composition and seasonal abundance.\nIce. Agri. Sci. 20, 73-80.\n[23] Soulsby, E.J.L. (Ed.), 2006. Helminths, Arthropods and Protozoa of\nDomesticated Animals, Baillier Tindall, UK. pp. 720.\n[24] Taylor, M.A., Coop, R.L., Wall, R.L. (Eds), 2007. Veterinary\nPararsitology. Blackwell Science Ltd. Oxford, UK. pp, 224-234.\n[25] Thrusfield, M. (Ed.), 2008. Veterinary Epidemiology. Blackwell\npublishing, London, UK. pp, 178.\n[26] Yakhchali, M. and E. Golami, 2008. Eimeria infection (Coccidia:\nEimeriidae) in sheep of different age groups in Sanandaj city, Iran.\nVeterinarski Arhive 78: 57-64\n[27] Yakhchali, M. and M.R. Zarei, 2008. Prevalence of Eimeria infection in\nsheep of Tabriz suburb, Iran. Iranian Journal of Veterinary Research, 9:\n277-280\n[28] Zajac, A.M., Conboy, G.A. (Eds.), 2006. Veterinary Clinical Parasitoloy.\nBlackwell publishing, USA. pp, 3-4."]}